Impact of renal function decline on nutritional status in older adults: A cross-sectional analysis - Rasyid, Haerani; Savina, Rizki; Zainuddin, Andi Alfian; Ramadhan, Sitti Rabiul Zatalia; January, Rima; Sudarso, Agus; Faridin, Achmad Fikry Faridin (Acta Biomedica Atenei Parmensis, 2025)
Introduction: Nutrition is a key factor in maintaining health and overall well-being, particularly in older adults. One of the critical areas affected by insufficient nutrition is the decline in renal function, which can exacerbate other health issues. Decreased renal function in the elderly is due to physiological processes accompanied by changes in the anatomical structure of the kidney, such as progressive nephrosclerosis (glomerulosclerosis, tubular atrophy, and atherosclerosis). Malnutrition correlates with decreased renal function due to inadequate nutritional needs such as vitamins, proteins, and minerals that can exacerbate impaired renal function. Methods: This study was conducted from February 2024, to September 2024, with two primary locations: Panti Werdha Makassar, a care home for the elderly, and Posyandu Lansia, a health service center for older adults. The sampling type is using consecutive sampling.Results: TThis study was conducted on 100 elderly subjects. Subjects with abnormal UAC were found more in the CKD group (50%) than the non-CKD group (35%) (p: 0.005; OR; 5,714). Subjects with abnormal WC were found more in the non-CKD group (36%) than the CKD group (34%) (p: 0.175; OR: 0.547). Subjects at risk of malnutrition were more prevalent in the CKD group (33%) than the non-CKD group (23%) (p: 0.028).Conclusion: The elderly patients in this study had a complex profile with a high incidence of malnutrition and decreased renal function. This indicates the need for a multidisciplinary approach in the care of elderly patients, focusing on nutritional assessment, chronic condition control, and comprehensive management to improve quality of life and prevent further complications. (www.actabiomedica.it)